PERWUJUDAN KONTRA RADIKALISME DI PONDOK PESANTREN AL-KARIMIYAH DEPOK - Ari Pratama Putra (Universitas Islam Depok, 2023)
With the claims of terrorist nests to pesantren, the reputation of Islamic educational institutions has become negative. There needs to be a new breakthrough in managing Islamic educational institutions to improve their reputation. One of them is implementing an educational model that counters radicalism in the pesantren environment, because pesantren as an Islamic educational institution with an open ideology and will easily accept differences. One of the pesantren that implements a counter-radicalism education model is the Al-Karimiyah Islamic Boarding School, Sawangan Baru, Sawangan, Depok City. So, the author is interested in researching the pesantren. This study uses qualitative by emphasizing field studies (field research). This research begins with social construction which is inter-subjective, diverse and requires an overall understanding and inter-subjective relationship of symptoms. The results show that the process of realizing counter-radicalism values ​​at the Al-Karimiyah Islamic Boarding School is through programs and management that lead to that goal. Furthermore, Islamic programs and studies fostered in Islamic boarding schools produce students who are tolerant and sociable.